Investment priorities for research and innovation in urban agri-food systems: Toward more resilient cities in the Global South - Prain, Gordon; Simon, David; Halliday, Jess; Drechsel, Pay (Frontiers in Sustainable Food Systems, 2022)
Urban and peri-urban agriculture (UPA) is widely distributed throughout the Global South. Despite urban population growth and diversifying food habits, UPA delivers an important part of urban food supply, as well as other types of services to cities, such as employment and waste reuse. Nevertheless, the extent and importance of UPA varies between different urban areas, while challenges like limited recognition, land conversion, and water pollution and competition threaten the potential of UPA to contribute to urban resilience. Key investment priorities for research and innovation for overcoming current challenges include incentivized peri-urban zoning, urban allocation of productive lands, and increasing capacities for controlled environment agriculture (CEA). Innovative repositioning of food marketing can help to strengthen supply of healthy food from UPA production, increase decent employment, and turn food markets into nutrition hubs. Priority innovations for contributing to the circular bioeconomy of cities include scaling the safe use of wastewater for irrigation through investments in the adoption of multiple risk-barrier approaches and scaling UPA-based ecosystem services for valorising solid waste and environmental management. Innovations in urban governance are required to support these processes by bringing food systems into urban planning through food mapping and the multisectoral platforms for dialogue and policy formulation across city regions and with vertical levels of government.